Socio-psychological characteristics elections with weak content - I. V. Groshev; A. V. Gorbenko; V. V. Lukin; I. V. Antonenko (Вестник университета)
The socio-psychological features of elections with a weak content have been considered. The factors of interest of the electorate in such elections have been allocated. The main socio-psychological features of elections with a weak content, that determine the effectiveness of the use of political technologies have been noted. The causal typology of the features of elections with weak content, including formal, socio-psychological and political-technological features, has been presented. The process of effective information support of the election campaign has been analyzed and the conclusion has been made about the need for quality monitoring of candidates ‘ ratings in any election campaign. Conclusions have been drawn about the possibility of using the identified socio-psychological features of elections with low content in election campaigns.